(untitled) (Third Sector Social Economic Review, 2019)
Anthropology is human and cultural science. On the other hand culture is an accumulation of knowledge. Culture of war has reached today’s level as a result of this accumulation. Albert Einstein once said that I do not know what the third world war would be, but the fourth one would definitely be done with stones and sticks. Violence has always existed in man. What is the basis of conflict and violence is always discussed. Although there are different explanations in different beliefs, basic does not change. Eventually there is a clash of good and evil.it has always been a curiosity where the culture of violence and war came from.Unfortunately, we do not have the final documents on the first exit of violence. There are only first beliefs about violence and some simple combat tools. But it is possible to reach some conclusions by interpreting the beliefs and findings at hand.